Gauge Theory of Elementary Particle Physics - Cheng, Ta-Pei (Oxford University Press, 1984)
The aim of this book is to provide student and researcher with a practical introduction to some of the principal ideas in gauge theories and their applications to elementary particle physics. Elementary particle physics has made remarkable progress. We have a comprehensive theory of particle interactions. One can argue that it gives a complete and correct description of all non-gravitational physics. This theory is based on the principle of gauge symmetry. Strong, weak, and electromagnetic interactions are all gauge interactions. A knowledge of gauge theory is essential for anyone interested in modern high energy physics. Regardless of the ultimate correctness of every detail of this theory, it is the framework within which new theoretical and experimental advances will be interpreted in the foreseeable future.